Improving the Ability to Recognize Numbers through Number Flannel Board Media in Group a Children of PAUD Rois Wali 2, Sukaresmi District - Nurrohilah, Siti; Sumiati, Enok; Khoirunisa, Melani; Nurbaiti, Zakia; Nurkhosyiah; Aprilianti, Via; Sofyan, Yayan (Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to determine the effectiveness of using flannel boards in improving number recognition skills in children in Group A of the Rois Wali 2 Sukaresmi Early Childhood Education Center. This study uses a Classroom Action Research (CAR) approach, which was carried out in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were children aged 4–5 years who were members of Group A of Rois Wali 2 Sukaresmi Early Childhood Education. The research instruments included observation sheets, field notes, and documentation of learning activities. The results showed that the use of flannel board media significantly improved children's ability to recognize numbers. In the first cycle, most children were able to stick numbers in sequence with the teacher's guidance, while in the second cycle, children were able to match numbers with the number of objects correctly and arrange numbers in sequence. In addition to cognitive abilities, children's learning motivation also increased, as seen from their enthusiasm, focus, and confidence during learning. Based on these findings, it can be concluded that flannel board media is effective in improving number recognition skills while holistically building the learning motivation of early childhood.